THE IMPACT OF MSCI ESG RATINGS ON STOCK MARKET BETA: A CASE STUDY OF DEVELOPED AND EMERGING MARKETS - Vichsanzy, Falahariq; Nainggolan, Yunieta Anny (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study examines the impact of MSCI's Environmental, Social, and Governance (ESG) ratings on stock market beta among publicly listed companies in developed and emerging markets. Utilizing a quantitative research design, data from 459 companies across 11 sectors were analyzed, incorporating the latest five MSCI ESG ratings and corresponding five-year beta coefficients as measures of stock beta or systemic risk. Descriptive statistics and correlation analyses were conducted to assess the relationship between ESG ratings and stock market beta. The findings reveal that while companies in developed markets have higher average ESG ratings compared to those in emerging markets, they also exhibit greater stock beta. Sector analysis indicates that industries such as Real Estate and Financials demonstrate strong ESG performance and lower stock beta, whereas sectors like Materials and Health Care show higher volatility regardless of their ESG ratings. Correlation analysis shows a very weak relationship between ESG ratings and stock beta, suggesting that ESG ratings are not strong predictors of stock market beta. In conclusion, the study finds that ESG ratings alone do not significantly impact stock market beta. It recommends that investors integrate ESG considerations with traditional financial analysis for better investment decisions. Companies should continue to enhance their ESG practices for sustainability and reputational benefits, even if it does not directly reduce stock beta. Policymakers, particularly in emerging markets, might focus on strengthening ESG frameworks to support sustainable investment environments.